Plant health progress for boosting food security - Volosciuc, L. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2024)
Starting from increasing the impact of phytosanitary agents and deepening the ecological problems caused by their combat, it becomes rational to change the paradigm of the protection of plants with their health. The purpose of the paper is to highlight and establish the role of the main factors that are the basis of plant health and how they determine the phytosanitary status of agroecosystems and the degree of food security. Research methods and methodology are oriented to the identification and determination of the biological peculiarities of agents, as well as the biological, ecological and economic analysis of protection means of agricultural crops. As effective measures in promoting plant health, it is proposed to apply the link between soil, plant and human health, the role and place of GMOs in solving phytosanitary problems, the perspectives of genome editing, the expansion of the implementation of regenerative agriculture. In order to overcome this problem, the paper contains information on the possibilities of application of synergic phenomena in plant protection, the interaction between which provides a significant increase in performance indicators and stability of the system state. The article describes the role and place of several factors: link between soil, plant and human health, the role and place of GMOs in addressing phytosanitary issues, prospects for genome editing, activities to extend the implementation of regenerative agriculture, synergic phenomena as direction to increase the effectiveness of plant protection means and other phenomena that determine food security and food safety, the achievements of the institute in the direction of the development and implementation of biological means of plant protection, especially biological preparations.